Mild and efficient method for the synthesis of vinylogous carbamates from alkyl azides - Reddy, D. Srinivasa; Rajale, T. V.; Shivakumar, K.; Iqbal, Javed (Tetrahedron Letters, 2005)
A mild and efficient one-pot method for the synthesis of vinylogous carbamates is reported starting from alkyl azides under a hydrogen atmosphere using 10% Pd/C. The resulting products are useful intermediates for the synthesis of heterocyclic compounds, natural products, and in peptidomimetics. (C) 2004 Elsevier Ltd. All rights reserved.